Copper‐Catalyzed Amination of Congested and Functionalized α‐Bromocarboxamides with either Amines or Ammonia at Room Temperature. Issue 38 (15th August 2017) - Ishida, Syo; Takeuchi, Kentaro; Taniyama, Nobuhiro; Sunada, Yusuke; Nishikata, Takashi
Abstract: There are several reports on the synthesis of alkylamines, but most of the reported methods are not suitable for the synthesis of hindered amines. In this research, we found that a copper catalyst is effective for the formation of congested C−N bonds at room temperature. Control experiments revealed that a copper amide is a key intermediate. Moreover, when a chiral amine was used, a quaternary carbon stereogenic center was created with good selectivity. Abstract : Bulk up : A copper catalyst system enables the reaction of bulky and functionalized alkyl groups with amines, including ammonia, at room temperature. The key intermediate in this amination reaction is a copper amide.